Pengaruh Pajak Daerah dan Retribusi Daerah Terhadap Kemandirian Keuangan Daerah di Pemerintah Kota Tasikmalaya - Rima Novianti; Yeti Apriliawati (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Tasikmalaya City Government is one of several regions in Indonesia that has implemented regional autonomy. However, in practice, the regional autonomy of the Tasikmalaya City Government has not been implemented optimally. This is reflected in the still low contribution of the regional revenue, which is influenced by issues in the local taxes and regional levies sector. The objective of this research was to find out the influence of local taxes and regional levies on regional financial independence in the Tasikmalaya City Government. This research used quantitative methods based on secondary data obtained from the Tasikmalaya City Government Budget Realization Report for the 2016-2020 period. The results indicate that the regional financial independence in the Tasikmalaya City Government was significantly influenced by local taxes and regional levies, both partially and simultaneously.